Chemical profiles of PM emitted from the iron and steel industry in northern China. (February 2017) - Guo, Yangyang; Gao, Xiang; Zhu, Tingyu; Luo, Lei; Zheng, Yang
Abstract: Source-level sampling methods were adopted in this study to sample six iron and steel plants referring four main manufacturing processes, with over 150 samples collected and measured in this study, the latest data for iron and steel industry in China has been demonstrated. The emission factors of CO2, CO, SO2, NO x, TSP, PM2.5 and PM10 were calculated, and the majority of pollutants were emitted from the sintering process. The virtual impactor divided the PM sample into three size fractions for chemical profiles and the profiles indicate that SO4 2−, NH4 + and OC distribute more into fine particles. The elements in PM from the sintering, pelletizing, puddling and steelmaking processes were measured and compared using the coefficient of divergence. The divergence between PM2.5 and PM10 for the same process is not obvious, with CD values ranging from 0.1697 to 0.2578. PM2.5 profiles of four process were notably different from one another, with CD values ranging from 0.4802 to 0.7500. More efforts are needed to update the PM profiles in China. PAHs in PM were investigated, and most of the PAHs in PM are from the sintering process. The total PAH concentration in PM2.5 from the sintering process is 73.28 ± 1.45 μg/m 3 with a BaPE value calculated at 9.92 μg/m 3 . Highlights: PM2.5 and PM10 profiles were obtained by source-level sampling from six plants. Emission factors comparison reflects the influences caused by control facilities. Sintering is the main emission source especially the toxic PM2.5 and PM10. PAHs levels and profiles for PM were analysed with BaPE value calculated.